Environmental enrichment may protect against hippocampal atrophy in the chronic stages of traumatic brain injury - Miller, Lesley S.; Colella, Brenda; Green, Robin E. (Frontiers in Human Neuroscience, 2013)
Objective: To examine the relationship between environmental enrichment (EE) and hippocampal atrophy in the chronic stages of moderate to severe traumatic brain injury (TBI). Design: Retrospective analysis of prospectively collected data; observational, within-subjects. Participants: Patients (N=25) with moderate to severe TBI. Measures: Primary predictors: (1) An aggregate of self-report rating of EE (comprising hours of cognitive, physical, and social activities) at 5 months post-injury; (2) pre-injury years of education as a proxy for pre-morbid EE (or cognitive reserve). Primary outcome: bilateral hippocampal volume change from 5 to 28 months post-injury. Results: As predicted, self-reported EE was significantly negatively correlated with bilateral hippocampal atrophy (p<.05), with greater EE associated with less atrophy from 5 to 28 months. Contrary to prediction, years of education (a proxy for cognitive reserve) was not significantly associated with atrophy. Conclusion: Post-injury EE may serve as a buffer against hippocampal atrophy in the chronic stages of moderate-severe TBI. Clinical application of EE should be considered for optimal maintenance of functioning in the chronic stages of moderate-severe TBI.